Sector mapping method for 3D detached retina visualization. Issue 134 (October 2016) - Zhai, Yi-Ran; Zhao, Yong; Zhong, Jie; Li, Ke; Lu, Cui-xin; Zhang, Bing
Highlights: A new sector-mapping algorithm was introduced. We further improved our previous retinal detachment 3D reconstruction work in this paper. Simulation and data analysis were done to prove the effectiveness of new algorithms. Abstract: A new sphere-mapping algorithm called sector mapping is introduced to map sector images to the sphere of an eyeball. The proposed sector-mapping algorithm is evaluated and compared with the plane-mapping algorithm adopted in previous work. A simulation that maps an image of concentric circles to the sphere of the eyeball and an analysis of the difference in distance between neighboring points in a plane and sector were used to compare the two mapping algorithms. A three-dimensional model of a whole retina with clear retinal detachment was generated using the Visualization Toolkit software. A comparison of the mapping results shows that the central part of the retina near the optic disc is stretched and its edges are compressed when the plane-mapping algorithm is used. A better mapping result is obtained by the sector-mapping algorithm than by the plane-mapping algorithm in both the simulation results and real clinical retinal detachment three-dimensional reconstruction.